Democracy in contemporary Egyptian political discourse - Dunne, Michele Durocher (Discourse approaches to politics, society, and culture, 2003)
When politicians and pundits in the Middle East discuss democracy, do they mean it? Looking at public discourse about democracy in contemporary Egypt, Dunne proposes a fresh way of reading Arabic political discourse. She charts a method combining ethnographic research into communities of people producing political discourse with investigation of the texts themselves, using tools from anthropology, pragmatics, and sociolinguistics -- a method with broad applicability to political discourse generally. Taking off from the premise that all discourse is based in social interaction, this book demonst.